Pajak Pertambahan Nilai Terhadap Jasa Pendidikan: Upaya Mendukung Pemerataan Pendidikan - Lola Inganta Saragih; Padhilah Dikri; Kuat Sidik Wahyono; Suparna Wijaya (Politeknik Keuangan Negara STAN, 2022)
This study attempts to examine the impact of changes to the taxation scheme for VAT on educational services. Education services which were originally excluded from VAT objects resulted in quite large tax expenditures but their implementation has not been on target. The HPP Law changed the taxable service exemption scheme to provide VAT facilities in the form of exemption or not being collected. Research using descriptive qualitative method. To ensure that the provision of these facilities is right on target, the government needs to determine a certain classification for the provision of educational services with a regulation the preparation of which is coordinated with the relevant technical ministries. This research is expected to be a reference for stakeholders in formulating policies in order to realize the principles of justice and equity in education and optimize government revenues. Penelitian ini berusaha mengkaji dampak dari perubahan skema pemajakan atas PPN Jasa Pendidikan. Jasa pendidikan yang semula dikecualikan dari objek PPN menimbulkan belanja perpajakan yang cukup besar namun implementasinya belum tepat sasaran. UU HPP mengubah skema pengecualian jasa kena pajak menjadi pemberian fasilitas PPN berupa pembebasan atau tidak dipungut. Metode penelitian yang digunakan adalah kualitatif deskriptif. Untuk memastikan pemberian fasilitas ini tepat sasaran, pemerintah perlu menetapkan klasifikasi tertentu atas penyelenggaraan jasa pendidikan dengan suatu aturan yang penyusunannya dikoordinasikan dengan kementerian teknis terkait. Penelitian ini diharapkan dapat menjadi acuan bagi pemangku kepentingan dalam perumusan kebijakan demi terwujudnya asas keadilan dan pemerataan pendidikan serta optimalisasi penerimaan negara.